Strategi Komunikasi Persuasif Da'i Dalam Penggunaan Bahasa Jawa Krama Untuk Meningkatkan Keimanan Jamaah - Silvi Armelia; Khomsarial Romli; Ade Nur Istiani (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2026)
This study analyzes the stages of persuasive communication strategies used by preachers (da'i) through Krama Javanese to enhance congregational faith at Istiqlal Mosque, Central Lampung. A qualitative descriptive field research approach was applied. Data were collected through semi-structured in-depth interviews, non-participant observation, and documentation. Informants were selected using purposive sampling: preachers, mosque administrators, and congregation members. Data analysis employed an interactive model supported by simple quantitizing to strengthen qualitative findings. The results reveal three stages of persuasive communication strategy: formulation (understanding the congregation's background and selecting Krama Javanese), implementation (delivering messages politely, without coercion, with real-life examples), and evaluation (observing changes in understanding and worship behavior). Quantitizing results show an average comprehension score of 4.7 and behavioral change score of 4.3 on a 5-point scale. Triangulation across three sources confirms consistent findings. This strategy aligns with Aristotle's ethos, pathos, logos and the Elaboration Likelihood Model. The study concludes that using Krama Javanese effectively increases congregational faith, reflected in improved quality of mahdhah worship such as congregational prayers and Qur'anic recitation. This research contributes to understanding how local language integration in persuasive communication can strengthen emotional proximity between preachers and congregations while enhancing religious practice quality.